anonymous
  • anonymous
graph 6x^2 +11x - 35
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
can anyone help
anonymous
  • anonymous
??
anonymous
  • anonymous
hello

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
https://www.desmos.com/calculator
MrNood
  • MrNood
this is a quadratic equation - its graph is a parabola if you want to sketch it then if the value in front of x is positive then it is U shaped, if negative then it is inverted U If you set x = 0 in the equatin - that will give oyu the vlue where it crosses the Y axis if you solve the quadrtic =0 then that will give you the place where it crosses the X axis that is enough to sketch it
anonymous
  • anonymous
6x^2 + 11x -35 = 0 Factor. To do this, Multiply -35 and 6 and get -210, Now what two numbers multiply to -210 and add up to 11 (the coefficient of the middle term)? Answer 21 and -10 So break the 11x into two terms. 6x^2 + 21x -10x -35 = 0 Group (6x^2 + 21x) + (-10x -35) = 0 Factor like terms 3x(2x + 7) + -5(2x + 7) = 0 Then factor out the (2x + 7) for (2x + 7)(3x - 5) = 0 so set each term = 0 and get x = 5/3 or x = -7/2
anonymous
  • anonymous
6x² + 11x - 35 = 0 6x² - 10x + 21x - 35 = 0 2x(3x - 5) + 7(3x - 5) = 0 (3x - 5) (2x + 7) = 0 3x - 5 = 0 OR 2x + 7 = 0 x = 5/3 or x = -7/2
anonymous
  • anonymous
6x^2 + 11x -35 = 0 6x^2 -10x + 21x -35 = 0 2x(3x-5)+7(3x-5)=0 (2x+7)(3x-5)=0 2x=-7 or 3x=5 x=-7/2 or x=5/3

Looking for something else?

Not the answer you are looking for? Search for more explanations.